Design and Validation of a Competency Development Model for Digital Transformation Leadership in the Banking System - Ahmadi Khesal, Ahmad; Vedadi, Ahmad; Gholamzadeh, Dariush (Management Strategies and Engineering Sciences, 2025)
The present study aimed to design and validate a competency development model for digital transformation leadership in the country's banking system. This research follows an exploratory mixed-methods approach. The qualitative phase employed thematic analysis, while the quantitative phase utilized a survey research method. The statistical population in the qualitative section consisted of 15 banking system experts, selected through purposive sampling based on the principle of theoretical saturation. In the quantitative section, the statistical population included bank managers and supervisors across the country, from whom a sample of 335 individuals was selected using stratified random sampling. In the qualitative phase, data collection was conducted through field research using semi-structured in-depth interviews. Similarly, in the quantitative phase, data collection was also based on field research, utilizing a researcher-developed questionnaire. Data analysis in the qualitative phase was performed using coding techniques, while in the quantitative phase, descriptive and inferential statistical methods were employed. The results indicated that digital leadership competencies include individual characteristics, digital intelligence, and digital capability/capacity. Additionally, competency development methods comprise self-learning, virtual training, experience transfer, coaching and consulting, role-playing, behavior analysis, job rotation, on-the-job training, workshops, mentoring, and career path planning. The findings also revealed that bank managers possess the necessary competencies and are in a favorable state.